Evaluation of CMS's Federally Qualified Health Center (FQHC) Advanced Primary Care Practice (APCP) Demonstration Final Second Annual Report - Kahn, Katherine L. (RAND Corporation, 2015)
The Department of Health and Human Services, acting through the Centers for Medicare and Medicaid Services, implemented a three-year project intended to support the transformation of federally qualified health centers (FQHCs) into advanced primary care practices (APCPs) in support of Medicare beneficiaries. RAND is assessing the effects on access, quality, and cost of care provided to Medicare and Medicaid beneficiaries.